(untitled) - Evans, Mike (Hoboken, New Jersey, 2017)
Achieve with Accountability presents a recipe for awakening the whatever it takes attitude to achieve what matters most to individuals, teams and organizations. Discover how to transform accountability into a positive, engaging and forward looking experience that will secure your position in the new world of work. Learn how to kick-start a revolution that will blast your team or organization to new heights of success. We are in a brawl with no rules, where the fast, flexible and agile will eat and spit out the slow, over-thinking and complacent. When you relinquish accountability you place your future in the hands of other people or events. It's only by taking accountability and ownership for our circumstances that we can achieve what matters most. Embrace the accountability fundamentals that have helped individuals, teams and organizations for years to achieve and exceed what matters most.
Keywords: Lãnh đạo,Leadership